PENENTUAN JUMLAH PENYALURAN DANA BOS PADA MTs MENGGUNAKAN ALGORITMA NAIVE BAYES - Nurul Afriani Tanjung; M.Irwan Padli Nasution; Ali Ikhwan (UIN Sumatera Utara Medan, 2021)
School Operational Assistance (BOS) has an important contribution to increase access to education in Indonesia. Deli Serdang Regency is a district that has a large number of residents, schools and students with a large number of schools and students, so sometimes the budget funds for BOS funds are not sufficient to provide all schools with the total number of students listed in the madrasah emission data. With the lack of government budget for BOS funds, a cut in the distribution of BOS funds was carried out in each school which was usually done manually by only looking at the number of students registered in the EMI data and determining the percentage of distribution of BOS funds to each school regardless of the needs that must be met at the school. In this final project, the researcher makes a data mining system for determining the amount of distribution of BOS funds in Deli Serdang Regency, this system is built using the Naive Bayes algorithm as a means of calculating BOS funds according to predetermined criteria, this system uses the PHP programming language using the CodeIgniter framework and MySQL as database method used in this system is waterfall. This system was built with the aim of making it easier to distribute and so that the distribution of BOS funds is right on target to schools in need.